Guidelines, recommendations, and near future for university libraries - Sanches, Tatiana (2022)
In the current context, library associations around the globe seek to present perspectives for the future, supporting professionals to develop strategies, projects, and skills. In Portugal, the Recommendations for Higher Education Libraries have given impetus to the work of professionals to face changes and continue their intervening and active role. At the same time, they aim to serve as a focus, creating national congruence in the areas of activity, and as an inspiration for action, motivating a convergence of information professionals, to contribute to greater unity and coherence of Higher Education Libraries in Portugal. This is the basis for this exploratory study. To this end, a literature review that embases a case study is carried out to understand the librarian's professional strategies that have been used throughout the Portuguese academic community. How do institutions and their professionals position themselves to support and develop actions around future challenges? How is being developed the support for teaching and learning, specifically in promoting information literacy skills and fostering digital fluency and user empowerment? How is addressed the support for research activities and scientific publication, especially in the context of Open Science? How is professional and organizational development that places the librarian at the center of processes and institutions as aggregators of synergies for continuous improvement actions? And finally, how are being taken projects to the design and provision of services and partnerships that facilitate and enhance the creation of networks for cultural expression, including the preservation and dissemination of documentary heritage.It is concluded that the preparation and planning based on guidelines work as stabilizers, which anchor the actions developed, at the same time that the winds of change allow the exploration of new paths and practices, thus enhancing a virtuous context of action.